Atmospheric carbonyl compounds in a tropical urban area: Levels, occurrence, and Monte Carlo-based health risk assessment - Mateus S. Moreira; Lícia P. S. Cruz (Air Quality, Atmosphere & Health, 2026)
Abstract Carbonyl compounds (CCs) are relevant atmospheric pollutants due to the high toxicity and carcinogenicity of some species. This study assessed the lifetime carcinogenic (LCR) and non-carcinogenic (hazard quotient, HQ; hazard index, HI) risks for three age groups exposed by inhalation, using Monte Carlo simulations based on CCs’ atmospheric levels measured at seven sites in Salvador, Brazil, during the rainy and dry periods. Ten CCs were passively sampled and determined by HPLC-UV. Formaldehyde (FA) and acetaldehyde (AA) predominated, accounting for approximately 55% and 61% of total concentrations in the rainy and dry periods, respectively. Higher molecular weight carbonyls predominated at heavy-duty traffic sites, reflecting Brazil’s vehicular fuel matrix, which favors both direct emissions and secondary photochemical formation of CCs. FA concentrations exceeded the TCEQ long-term exposure limit (3.30 µg m − 3 ) at all sites and periods, reaching up to 7.4 times this limit during the dry period. At the 95th percentile, LCR values for FA and AA exceeded the USEPA lower acceptable limit (1.0 × 10 − 6 ) for all age groups, and FA (up to 3.49 × 10 − 5 ) exceeded the WHO upper limit (1.0 × 10 − 5 ), especially among adults. Deterministic LCR values fell within the 60th–75th percentile range of the probabilistic distributions, indicating that this conventional method underestimated cancer risks. For acrolein, the HQ (P95) was fourfold above the USEPA limit (HQ ≤ 1) in children, and the cumulative HI (P95) exceeded this limit across all three groups. These results showed that no age group is fully protected, highlighting the need to include FA, AA, and acrolein in Brazilian air quality standards, to implement stricter controls on vehicle emissions, and to establish extensive, continuous atmospheric monitoring.